Isolation and characteristic of biphenyl degrading bacteria from mangrove enviroment - Shamala Nair, D/O Balen (Universiti Malaysia Sarawak (UNIMAS), 2012)
Polychlorinated biphenyls (PCBs) and biphenyl often used in the chemical industry as dielectric fluid and plasticizer. It is known to be recalcitrant due to the presences of chlorine in the molecules. The aim of the study is to isolate and characterize the biphenyl degrading bacteria by using the molecular and biochemical test. The bacteria strain was isolated from the mangrove environment in Bako National Park. In this study, the isolation of biphenyl degrading bacteria was attempted using the ONR7a media which containing biphenyl as the sole carbon sources for the selection. Four different strains were succefully isolated which named as Sl, S2, S3 and SS. Further characteristic of the enzymes and the degradation pathway of putative degrader were investigated by undergo the oxidase test, catalase test, motility test, MRVP test and also the gram staining. From the gram staining we can conclude that all four strains that obtain are gram negative bacteria. All four strains are non-motile bacteria which have a positive result in catalase and oxidase test. In the molecular characterization and succefully amplifying the 16S rRNA gene sequences (lSOObp) from the extracted DNA of the bacteria by using the PCR method. From the blast search it showed that the bacteria identified for S 1 is Marinobacter sp.strain Trimyema-2 with 1423bp was successfully sequenced. Next, for the S2 bacteria strain, the result showed that 1347bp was successfully sequences of Salipiger sp strain BH8S027. Then, the strain S3 was known as Thioc/ava sp.strain VS-126 with 1370bp was successfully sequences from this bacteria strain. Lastly, for the sample SS, the sequences of the bacterial strain showed highest homology toward Mycoplana sp. Strain GII0. Further study on the enzymes of all the four strain which was isolated could produce a valuable commodity for biochemical industry.